Green human resource management: A two-study investigation of antecedents and outcomes. Issue 7 (25th February 2020) - Shafaei, Azadeh; Nejati, Mehran; Mohd Yusoff, Yusmani
Abstract : Purpose: The study aimed to provide insights on antecedent and outcome of green HRM at the organisational level and the outcome of green HRM at the individual level. It also sought to examine the mechanism through which green HRM would lead to employees' positive outcome. Design/methodology/approach: A quantitative study design using a two-study approach was employed to collect and analyse the data. For study 1, 206 hotels from Malaysia were included in analysis at the organisational level, while in study 2 at the individual level, 508 employees from different sectors provided insights through an online questionnaire. For both studies, partial least squares (PLS–SEM) was used to assess the research model. Findings: All the proposed hypotheses were supported. Specifically, at the organisational level, organisational environmental culture is positively related to green HRM, and green HRM management positively associates with organisation's environmental performance. At the individual level, green HRM positively influences employees' job satisfaction, and meaningfulness through work is a strong mediator in this relationship. Originality/value: This study is significant as it contributes to both theory and practice by providing fresh insights on green HRM and its antecedent and outcomes at two levels (organisational and individual) and across two economies (emerging and developed). It also sheds some light on the outcome of green HRM at the employee level which is an area that is still under-researched. By focusing on meaningfulness through work as an important factor, the study contributes to better understanding of green HRM and employees' positive outcomes.